Diseño de metodología para la evaluación de los impactos ambientales, sociales y económicos durante el ciclo de vida de un proyecto constructivo (2016)
This project is carried out with the purpose of designing a methodology to evaluate the environmental, social and economic impacts during the life cycle of a construction project in the city of Barranquilla. Impacts can be seen at different levels, such as mild, moderate or high, depending on the characteristics of the project during its generation, which is why it is necessary to clarify and identify the direct, potential and indirect impacts for the project execution, as well As the most practical ways to avoid or mitigate them. The legal implications of the misuse, abuse and deterioration of the environment, which is finally the stage that allows the execution of civil works, and small as they are, their construction in each of the Stages that involves, influences in an important way in the lifestyles, the culture and the society in general. The first stage of the project intends to initiate the actions aimed at undertaking the evaluation of the construction projects of buildings, sewage networks and pavement, through the direct observation research method, in which a perception of the object of the project is sought. Research and be able to design a methodology to identify and mitigate environmental, social and economic impacts on construction projects.